Inorganic spectroscopic methods - Brisdon, Alan K; Oxford University Press (Oxford ; New York : Oxford University Press, 2008)
An understanding of spectroscopic methods is needed for students in chemistry from the undergraduate level onwards. This text provides an introduction to common spectroscopic techniques and their application to inorganic compounds
Introduction -- Vibrational spectroscopy -- Resonance spectroscopy -- UV-visible spectroscopy -- Mass spectroscopy -- Putting it all together -- Answers to questions
Includes bibliographical references and index
Keywords: Inorganic compounds -- Analysis; Spectrum analysis